ACRA learning strategies scale: psychometric adaptation in Peruvian university students - Gonzales Córdova, Grecia Libertad (2020)
This study had as purpose of this is to adapt the Scale of Learning Strategies (ACRA) by Roman and Gallego (1994) for Private University students in San Juan de Lurigancho. A non-experimental design with a cross-sectional and psychometric test was used. Four hundred selected students took part of the probability sample, considering that the sample size was calculated on 95% of confidential interval and were distributed proportionally according to the academic and professional schools. Regarding the procedures, items analysis was carried out, so it could be subjected by five expert judges, who verified the validity of the test content. Therefore, the main compounds analysis were carried out, where KMO showed values from 0.86 to 0.91 and Barlett’s test of spherecity was minus 0.05 which allowed to verify the inner consistency through the Cronbach’s alpha measure and the Spearman-Brown formula, having values for each sub-scale, acquisition, codification, recovery of information and procedure support, from 0.71 to 0.92. In conclusion, there is enough evidence of validity and confidence of the instrument for its use. Additionally, percentile ranks were made and will be useful to identify the predominant learning strategies of the population survey and the following research that allows a better understanding of this variable.